On-line handwritten Chinese character recognition - Fan, Fang (2008)
The on-line recognition systems of handwritten Chinese characters are of great demand in many practical applications such as: pen-based computer, data input, signature verification and personal digital assistant, etc. In the past decade, though many great advances have been made in this area, due to a number of intrinsic difficulties in handwritten Chinese character (HCC) recognition, the recognition rate and the processing speed still cannot meet practical requirements.